PENGARUH KEPEMIMPINAN ISLAM DAN MOTIVASI KERJA ISLAM TERHADAP KINERJA KARYAWAN - Choiril Anam (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
This research raises the title of influence of Islamic leadership and the Islamic work motivation on the performance of BMT (Made) employees in Demak District. One of the obstacle which doesn’t make any advanced and the developed of BMT is the low performance of employees. The formulation of the problem in this research is whether there is a significant influence of Islamic leadership and the motivation of Islamic work on the performance of employees either partially or simultaneously on the performance of employees? This study aims to find out how much influence of Islamic leadership and work motivation and to know the most dominant influence between Islamic leadership and the work motivation on the performance of employees BMT Made in Demak District. This type of this research is field research by using quantitative methods. The population in the study there are 34 employees, who sampled 28 employees consisting of main employees and sub branch employees. The test used in analyzing the data (questionnaire) is a test of validity and reliability, and statistical tests that include; classical assumption test, F test and T test. The result of regression equation test is Y = 4.510 + 0.076 X1 + 0.679 X2, this means that employee’s performance variable get influence from Islamic leadership variable and work motivation with value equal to 0,079 and 0,679 every employee performance variable have 1 score increase. While for Islamic leadership T test obtained value of 0.533 2.060. This means that Islamic leadership variables do not have a significant influence and employee motivation partially have an influence on performance variable of BMT employees. F - test obtained value equal to 18.782, while F table 3,385, because F count > F table then simultaneous test or jointly variable of Islamic leadership and work motivation of Islam have influence to performance of BMT Made employee. Among the two independent variables that are most dominant in influencing employee performance variables is the Islamic work motivation with a value of 5.415. To improve employee performance, managers are expected to improve intensive communication with the employees and provide an opportunity to convey what the wishes and expectations of the employee are. On the other hand, managers must also open themselves to accept criticism or input that is constructive in order to improve the institution.